Hughes and Gleason's Virosaine A—Appreciating the Art in Synthesis. Issue 45 (11th October 2017) - Ellis, Bryan D.; Vanderwal, Christopher D.
Abstract : The synthesis of the Securinega alkaloid virosaine A by Hughes and Gleason is a perfect example of the intersection of art and chemical synthesis. An ingenious cascade reaction builds most of the polycyclic architecture, but necessitates a challenging C−H functionalization, which is ultimately accomplished by an unusual directed lithiation reaction.